2018
DOI: 10.1111/grow.12249
|View full text |Cite
|
Sign up to set email alerts
|

No Place Like Home? Graduate Migration in Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…The majority intends to stay in Germany, which is in line with the findings from previous studies. Based on DZHW data of 2004/2005 study cohort, Haussen and Uebelmesser () reported that 60.4% of the graduates live in Germany five years after graduation and that they live in the regions where they studied. Busch and Weigert () also reported a 70% stay rate in regions after ten years of graduation based on GSOEP 1980–2004 which the authors interpret as the creation of regional labour markets by the universities in German federal states.…”
Section: Datamentioning
confidence: 99%
“…The majority intends to stay in Germany, which is in line with the findings from previous studies. Based on DZHW data of 2004/2005 study cohort, Haussen and Uebelmesser () reported that 60.4% of the graduates live in Germany five years after graduation and that they live in the regions where they studied. Busch and Weigert () also reported a 70% stay rate in regions after ten years of graduation based on GSOEP 1980–2004 which the authors interpret as the creation of regional labour markets by the universities in German federal states.…”
Section: Datamentioning
confidence: 99%
“…This evidence could favor use of DBHP 11 as an instrument as DBHP is more likely to capture where the parents themselves grew up. Other research (Winters 2011;Haussen and Uebelmesser 2015) suggests that students develop location-specific capital in the area where they went to college. This research supports the use of DBE.…”
Section: Instrumental Variable Analysesmentioning
confidence: 99%
“…In Section 3, the possible determinants of 1 Marinelli (2013) considers the employment three years after graduation. Haussen and Uebelmesser (2015) analyze the determinants of graduates belonging to specific migration groups five years after graduation.…”
Section: Introductionmentioning
confidence: 99%